Apoptotic and proliferative characteristics of proliferation centers in lymph node sections of patients with chronic lymphocytic leukemia. Issue 3 (March 2014) - Sachanas, Sotirios; Levidou, Georgia; Angelopoulou, Maria K.; Moschogiannis, Maria; Yiakoumis, Xanthi; Kalpadakis, Christina; Vassilakopoulos, Theodoros P.; Kontopidou, Flora; Tsirkinidis, Pantelis; Dimitrakopoulou, Aglaia; Kokoris, Styliani; Dimitriadou, Evangelia; et al.
Abstract We have analyzed the immunohistochemical expression of a wide range of molecules along with the proliferation rate separately in the proliferation centers (PCs) and in the rest of the tumor area, in lymph node or spleen sections of patients with chronic lymphocytic leukemia (CLL). Fas, FasL and c-FLIP were observed both within and outside the PCs in all cases. However, only the difference in FasL expression between the PCs and the non-PC areas attained statistical significance. Median survivin expression in the PCs was higher compared to the non-PC areas. Cleaved caspase 3 was expressed at very low levels both within and outside PCs, while BCL-2 protein was expressed at high levels in all cases in both tumor compartments. Multivariate analysis demonstrated that concurrent overexpression of Fas/FasL/c-FLIP in the PCs was correlated with worse outcome for progression-free survival as well as for overall survival.